Effects of Sequence and Base Composition on the CD and TDS Profiles of i‐DNA. Issue 18 (24th March 2021) - Iaccarino, Nunzia; Cheng, Mingpan; Qiu, Dehui; Pagano, Bruno; Amato, Jussara; Di Porzio, Anna; Zhou, Jun; Randazzo, Antonio; Mergny, Jean‐Louis
Abstract: The i‐motif DNA, also known as i‐DNA, is a non‐canonical DNA secondary structure formed by cytosine‐rich sequences, consisting of two intercalated parallel‐stranded duplexes held together by hemi‐protonated cytosine–cytosine + (C:C + ) base pairs. The growing interest in the i‐DNA structure as a target in anticancer therapy increases the need for tools for a rapid and meaningful interpretation of the spectroscopic data of i‐DNA samples. Herein, we analyzed the circular dichroism (CD) and thermal difference UV‐absorbance spectra (TDS) of 255 DNA sequences by means of multivariate data analysis, aiming at unveiling peculiar spectral regions that could be used as diagnostic features during the analysis of i‐DNA‐forming sequences. Abstract : i‐DNA is an emerging non‐canonical DNA secondary structure that represents a suitable target in anticancer therapy. A multivariate data analysis unveiled peculiar TDS and CD spectral regions that could be used for the structural determination of i‐DNA‐forming sequences.